2020
DOI: 10.1021/acs.orglett.0c03460
|View full text |Cite
|
Sign up to set email alerts
|

Harpertrioate A, an A,B,D-seco-Limonoid with Promising Biological Activity against Alzheimer’s Disease from Twigs of Harrisonia perforata (Blanco) Merr.

Abstract: Harpertrioate A (1), an A,B,D-seco-limonoid with a rearranged ring B incorporating exocyclic C-30, was isolated from the EtOAc extract of Harrisonia perforata twigs. Its structure, including absolute configurations, was determined on the basis of spectroscopic data and X-ray crystallography. This compound exhibited biological activities against Alzheimer’s disease by reducing Aβ42 and Aβ40 production and shifting APP processing toward nonamyloidogenic pathway. The effect of 1 on the Aβ production was comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Western blot assays were performed according to the methods in our previous published studies [ 12 , 16 , 41 ]. In brief, cell lysates of U251-MAPT P301S cells were prepared, and protein concentration was determined with the BCA protein assay kit (Beyotime Institute of Biotechnology, P0012).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot assays were performed according to the methods in our previous published studies [ 12 , 16 , 41 ]. In brief, cell lysates of U251-MAPT P301S cells were prepared, and protein concentration was determined with the BCA protein assay kit (Beyotime Institute of Biotechnology, P0012).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as in our previous studies [ 14 , 38 , 39 , 56 ]. In brief, cell lysates of U251-APP cells were prepared using protein lysis buffer (Beyotime Institute of Biotechnology, P0013).…”
Section: Methodsmentioning
confidence: 99%
“…Among these avenues, inhibitors of amyloid precursor protein (APP) protease, β-site cleaving enzyme 1 (BACE1), and cyclin-dependent kinase 5 (CDK5) contributing to tau phosphorylation have been suggested as appealing drug targets for AD [ 9 , 10 , 11 , 12 ]. Previous studies have shown that natural products exhibited biological activities against AD by inhibiting cyclin-dependent kinase 5 and tau phosphorylation and reducing A β 42 and A β 40 production toward the nonamyloidogenic pathway [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the findings above and our previous studies, 21 we systematically investigated the GMs from the fruiting bodies of G. applanatum and isolated (±)-spiroganoapplanin A ( 1 ) possessing a complex 6/5/5/6/5/6-fused polycyclic skeleton (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%